PENERAPAN MODEL ECM: ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI KARET JAMBI PERIODE 2000-2021 - Diniawati Rahmatika (Transpublika Publisher, 2023)
Rubber is a type of plantation commodity that is part of the leading export commodity and generates a lot of profit for Indonesia's foreign exchange. One of the largest rubber producing centers in Indonesia is Jambi. However, the production of rubber in Jambi has fluctuated. Meanwhile, the potential size of the rubber trade market is very high. So it is feared that rubber production cannot keep up with the fulfillment of the domestic market and the international level. Then the purpose of this study is to analyze the factors that affect both the long term and the short term on rubber production in Jambi as a determinant of a more appropriate policy to enable an increase in its production. The method used in this research is Error Correction Mechanism (ECM) with the research period starting from 2000 to 2021. Based on the results of the research conducted, in the long term the variable of planting area and the number of superior seeds has a significant effect on rubber production in Jambi while the variable number of rubber farmers is not significant in influencing rubber production. Meanwhile, in the short term, only the variable number of rubber farmers has a significant effect on rubber production, while the variables of planting area and number of seeds are not significant in influencing rubber production.